Thermodynamics of Some Sodium Salts in Glycol + Water and Glycerol + Water Mixtures at Different Temperatures - Mohanty, P.C.; Nanda, B.B.; Chakraborty, C.; Misra, P.K. (Asian Journal of Chemistry, 2016)
The ion solvent interaction of NaCl, NaBr and NaI in glycol + water and glycerol + water at 10, 20 and 30% (w/w) within the temperature range of 30–40ºC have been inferred from conductance data. The dissociation constants K, DGº, DG°1, DG°t(el) have been computed and the ion-solvent interactions have been inferred.